Comparison of Students’ Achievement in Literary Appreciation Using Reciprocal Peer Tutoring and Conventional Teaching Methods - Augusta Chiedu Assimonye; Theresa Nnennaya Kanno (Journal Majelis Paspama, 2024)
Students’ poor achievement in Literature-in-English, particularly in the area of literary appreciation, has continued to be a major concern among educators and stakeholders in Nigeria. The conventional teacher-centered approach often limits students’ engagement, critical thinking, and interpretive skills, which are essential for understanding literary texts. To address this challenge, the study investigated the effect of Reciprocal Peer Tutoring (RPT) on students’ achievement in literary appreciation compared to the Conventional Teaching Method in public secondary schools in Anambra State. The study adopted a quasi-experimental pretest-posttest non-equivalent control group design to examine the effect of reciprocal peer tutoring (RPT) on students’ achievement and retention in Literature-in-English in Anambra State. Intact SSII classes were used, with 65 students randomly assigned to experimental and control groups. Data were collected using a validated and reliable Literature Achievement and Retention Test (LART). Trained teachers administered pretests, treatments, posttests, and retention tests over six weeks. ANCOVA was used to analyze data, controlling extraneous variables. The study ensured methodological rigor through standardized procedures, uniform lesson plans, and careful monitoring to achieve credible findings. The results showed that students taught literary appreciation using Reciprocal Peer Tutoring (RPT) had higher achievement scores than those taught with the conventional method. The RPT group (N=31) had a pretest mean of (41.24) and posttest mean of (68.83), with a mean gain of (27.59), while the conventional group (N=34) had a pretest mean of (32.70) and posttest mean of (35.61), with a mean gain of (2.91). ANCOVA results revealed a significant difference between the groups (F=211.397, P=0.00<0.05), leading to the rejection of the null hypothesis. Thus, RPT significantly enhanced students’ achievement in literary appreciation. It was concluded that Reciprocal Peer Tutoring significantly enhanced students’ achievement in literary appreciation. The study recommended that Literature-in-English teachers should adopt RPT to promote active learning, deeper comprehension, and improved performance among students.